The Effect of Carbon and Zinc Electrodes Using Sea Water Electrolyte on Air Battery Power - Sudarmanto Sudarmanto (SENATIK STT Adisutjipto, 2018)
The air-zinc battery uses oxygen from the atmosphere to produce electrochemical energy. After opening the battery into the air, oxygen diffuses into the cell and is used as cathode reagent. The air passes through the cathode to the active surface of the interior cathode in contact with the electrolyte liquid, namely sea water. On the active surface, the air cathode catalytically encourages the reduction of oxygen in the electrolyte liquid. This study aims to determine the effect of zinc anode on air batteries that are in direct contact with activated carbon as a source of electrical energy and find out the influence of electrolyte of seawater as an alternative source of electrical energy in air batteries. The research method uses Volta cells. Other advantages are safety and ecological benefits and low energy costs, as well as maximum power capability on environmentally friendly tolerance. In this study four salinity salinity was used, namely salinity of 3.56%, salinity of 3.99%, salinity 4.60% and salinity 5.02%. The results obtained are the highest voltage 1.144 Volt and the highest current of 4.85 mA is found in salt water salinity 5.02%.